Responses of serum chemokines to dramatic changes of air pollution levels, a panel study. (3rd October 2019) - Li, Yanli; Bonner, Matthew R.; Browne, Richard W.; Deng, Furong; Tian, Lili; Jim) Zhang, Junfeng (; Swanson, Mya; Rittenhouse-Olson, Kate; Farhat, Zeinab; Mu, Lina
Abstract: Background: Despite the in vitro and in vivo evidence, studies are limited in evaluating whether chemokines are potential inflammatory mediators in response to air pollution exposure in humans. Methods: We conducted a panel study coinciding with the Beijing Olympics, when temporary air pollution controls were implemented. We measured a suite of serum chemokines among healthy adults before, during and after the Olympics, respectively. Linear mixed-effect models were used to evaluate changes in chemokine levels over the three time periods. Results: In response to the 50% drop in air pollution levels during the games, levels of RANTES, MCP-2, and TARC decreased by 25.8%, 20.9% and 35.3%, respectively ( p  < 0.001) from pre-Olympics, and then increased by 45.8%, 34.9% and 61.5%, respectively ( p  < 0.001) after the games when air pollution levels went up again. Similar patterns were observed in subgroup analyses by sex, age, smoking and body mass index. GRO-α and IL-8 decreased significantly during the games (22.5% and 30.4%), and increased non-significantly after the games. Eotaxin-1 only increased significantly from during- to post-games. Conclusions: The strongest associations with air pollution levels were observed among RANTES, TARC and MCP-2. Those chemokines may play important roles in the air pollution-induced inflammatory pathway.